Prediction of Rupiah Currency Value Against Dollar with ARIMA Model - Bagus Dimas (UIN Sumatera Utara, 2021)
The currency of each country is different, resulting in difficulties in transacting between one country and another. So it takes a currency exchange process to facilitate a transaction process between countries called the Exchange Rate. However, exchange rate volatility can threaten the economy of a country. Therefore, a prediction of the exchange rate is needed so that investors or the public can determine strategies or plans for future economic policies. Therefore, this study aims to find the ARIMA model that has the best performance in predicting the rupiah exchange rate against the dollar. So that this model can be a reference for investors and the public in investing in shares with other countries. The results of this study obtained the best model, namely the ARIMA model (0, 1, 1) to predict the exchange rate for the next 20 periods with the help of eviews9 software.